Relevansi Gagasan Antonio Gramsci dalam Antropologi - A.A. Ngr. Anom Kumbara (Sunari Penjor : Jurnal of Anthropology, 2018)
The aims of this article is to explain relevance and contribution of Anthonio Gramsci views to Anthropology and cultural studies. Method in this study used liberary research. The result of this study that the cretical views of Anthonio Gramsci as neo-Marxism exponen are very important and relevance of antrophology and cultural studies, especially views of relationship between political, power and cultural, beside economy infrastructure factor as analysis based.